Fluorometric detection of tyrosine and cysteine using graphene quantum dots. Issue 39 (5th April 2016) - Li, Yan; Cai, Nan; Wang, Mengke; Na, Weidan; Shi, Fanping; Su, Xingguang
Abstract : A facile fluorescence method has been developed for the detection of tyrosine and cysteine based on graphene quantum dots as a sensitive probe. Abstract : Herein, a facile fluorescence method has been developed for the detection of tyrosine (Tyr) and cysteine (Cys) based on graphene quantum dots (GQDs) as a sensitive probe. Tyr could be oxidized to dopaquinone by tyrosinase catalyzation, which could efficiently quench the fluorescence of GQDs through an electron transfer process. However, Cys could act as tyrosinase inhibitors and reacted with the generated dopaquinones to give their polyphenol precursors. Therefore, the addition of Cys would make the fluorescence of above system recover. Under optimal conditions, a linear correlation was established between the fluorescence intensity and the concentration of Tyr in the range of 1.0–160 μmol L −1 with a detection limit of 0.5 μmol L −1 . The linear range for Cys was from 25 to 2000 μmol L −1 with a detection limit of 5.0 μmol L −1 . The fluorescence changes of the as-prepared GQDs as a function of the structure transformation during the interaction process provides a potential fluorescence based tool for monitoring Tyr and Cys.